(untitled) (Western Pacific Surveillance and Response, 2015)
Background: Middle East respiratory syndrome (MERS) is an illness caused by a coronavirus in which infected persons develop severe acute respiratory illness. A person can be infected through close contacts. This is an outbreak investigation report of the first confirmed MERS case in the Philippines and the subsequent contact tracing activities. Methods: Review of patient records and interviews with health-care personnel were done. Patient and close contacts were tested for MERS-coronavirus (CoV) by real time-polymerase chain reaction. Close contacts were identified and categorized. All traced contacts were monitored daily for appearance of illness for 14 days starting from the date of last known exposure to the confirmed case. A standard log sheet was used for symptom monitoring. Results: The case was a 31-year-old female who was a health-care worker in Saudi Arabia. She had mild acute respiratory illness five days before travelling to the Philippines. On 1 February, she travelled with her husband to the Philippines while she had a fever. On 2 February, she attended a health facility in the Philippines. On 8 February, respiratory samples were tested for MERS-CoV and yielded positive results. A total of 449 close contacts were identified, and 297 (66%) were traced. Of those traced, 15 developed respiratory symptoms. All of them tested negative for MERS. Discussion: In this outbreak investigation, the participation of health-care personnel in conducting vigorous contact tracing may have reduced the risk of transmission. However, being overly cautious to include more contacts for the outbreak response should be further reconsidered.